Distributed Fusion Estimation for Sensor Networks with Communication Constraints - Zhang, Wen-An; Chen, Bo; Song, Haiyu; Yu, Li (Springer Nature Singapore : Imprint: Springer, 2016)
This book systematically presents energy-efficient robust fusion estimation methods to achieve thorough and comprehensive results in the context of network-based fusion estimation. It summarizes recent findings on fusion estimation with communication constraints; several novel energy-efficient and robust design methods for dealing with energy constraints and network-induced uncertainties are presented, such as delays, packet losses, and asynchronous information... All the results are presented as algorithms, which are convenient for practical applications.